Effects of Parents’ Behavior on Children from an Islamic Perspective - Kinza Yasmeen; Dr. Saeed Ahmed (Journal of Religion and Society, 2025)
In Islam, parents hold a highly respected and influential position in shaping their children’s character, faith, and behavior. The Holy Qur’an and Hadith emphasize that the family is the first institution where a child learns values, manners, and the basics of faith. Therefore, parents’ attitudes and behavior deeply affect their children’s personality and future conduct. When parents show love, kindness, patience, and fairness, children grow up with emotional stability, self-confidence, and strong moral values.On the other hand, harshness, neglect, or favoritism can lead to feelings of insecurity, rebellion, or emotional imbalance in children. Islam encourages moderation neither excessive strictness nor total freedom so that children develop discipline along with respect and love for their parents. Moreover, parents are responsible not only for their children’s worldly upbringing but also for their spiritual and moral education. Parents must guide their children toward righteousness, prayer, honesty, and good behavior. In short, Islam teaches that the way parents behave through their words, actions, and treatment creates a lasting impact on their children’s hearts and souls. Loving guidance, good example, and spiritual nurturing help raise children who are respectful, pious, and successful in both this world and the hereafter. Keywords: Parents, Children, Behaviours, Responsibility